The Influence of Emotional Intelligence, Self-Efficacy, and Learning Motivation on Student Achievement - Zusmita Wasni, Nila; Sembiring, Dian Arisandy Eka Putra; Yusuf, Muhammad; Hendra, Robi; Febriyanti, Ella (Universitas Negeri Semarang, 2024)
Student achievement is not only determined by cognitive abilities, but also by non-cognitive factors that influence the student's learning process. In this case, emotional intelligence, self-efficacy, and learning motivation are important aspects that deserve attention. This study examines the influence of emotional intelligence, self-efficacy, and learning motivation on the achievement of Jambi University students. Quantitative research was conducted using Google Forms survey data from 360 students, which was determined by G-Power analysis. Data were analyzed using PLS-SEM. A significant relationship was found between the factors. Academic achievement is strongly influenced by emotional intelligence and self-efficacy (p < 0.05). In addition, emotional intelligence and self-efficacy increase learning motivation and academic achievement (p < 0.05). Academic achievement is moderately influenced by learning motivation. These findings emphasize the relevance of emotional intelligence, self-efficacy, and motivation for student success. These three factors significantly influence student academic success. Emotional intelligence helps students manage emotions and build positive social relationships. Self-efficacy encourages students' self-confidence in completing tasks. Learning motivation is the main driver that increases students' commitment to learning. The novelty of this research lies in the integration of emotional intelligence, self-efficacy, and motivation which are studied holistically to understand their influence on student achievement and the direct and indirect influence of emotional intelligence, self-efficacy, and learning motivation on academic achievement among students.